Intimate Partner Violence Victimization in the Cyber and Real World: Examining the Extent of Cyber Aggression Experiences and Its Association With In-Person Dating Violence - Marganski, Alison; Melander, Lisa (Journal of interpersonal violence, 2018)
This study explores the extent of cyber aggression victimization in intimate relationships and its co-occurrence with in-person experiences of psychological, physical, and sexual partner violence. Data were collected from 540 college students who reported being in a dating relationship in the past 12 months. Participants were asked to complete an online questionnaire that included measures assessing intimate partner victimization experiences in differing social contexts (through socially interactive technology and in face-to-face encounters). Findings indicated that intimate partner cyber aggression victimization is not uncommon, as nearly three quarters of respondents reported having experienced some form of it in the past year. Multivariate analyses also indicate that such aggression may be part of a larger violence nexus given its relation to in-person psychological, physical, and sexual partner violence victimization experiences. In light of these findings, it is recommended that longitudinal research encompassing multiple violence victimization experiences in varying social contexts is completed to determine whether online experiences foreshadow offline ones and, if so, consider interaction effects on outcomes as well as potential intervention strategies to reduce harm associated with such negative experiences.